(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
This study purposed to find out how the influence of E-Government variable with employee discipline variables in the Office of Communication and Informatics, Tana Toraja Regency. This study used quantitative research methods with descriptive research type. The sample were 19 people and the sampling method used saturated sampling technique. The data obtained were analyzed using simple linear regression analysis in a simultaneous and racial way. The results of this study showed that the results of the calculation of the percentage indicator variable of employee discipline at the Office of Communication and Information Technology of Tana Toraja Regency were in a good category with an achievement level of 73.75% which in the interpretation continuum the score was in the 80-100 interval or the agree / good category. the most influential indicators, namely the regulatory discipline indicator of 76.5%, then the discipline of responsibility of 74.10%, while the time discipline indicator got an average value of 69.75%, there was an influence of the E-Government variable on discipline. Employees at the Office of Communication and Informatics, Tana Toraja Regency amounted to 29.96%, while the rest was influenced by other factors not examined by researchers. Keywords: Effect of E-Government utilization, Employee Discipline